Drought responses of three closely related Caragana species: implication for their vicarious distribution. Issue 9 (18th March 2016) - Ma, Fei; Na, Xiaofan; Xu, Tingting
Abstract: Drought is a major environmental constraint affecting growth and distribution of plants in the desert region of the Inner Mongolia plateau. Caragana microphylla, C. liouana, and C. korshinskii are phylogenetically close but distribute vicariously in Mongolia plateau. To gain a better understanding of the ecological differentiation between these three species, we examined the leaf gas exchange, growth, water use efficiency, biomass accumulation and allocation by subjecting their seedlings to low and high drought treatments in a glasshouse. Increasing drought stress had a significant effect on many aspects of seedling performance in all species, but the physiology and growth varied with species in response to drought. C. korshinskii exhibited lower sensitivity of photosynthetic rate and growth, lower specific leaf area, higher biomass allocation to roots, higher levels of water use efficiency to drought compared with the other two species. Only minor interspecific differences in growth performances were observed between C. liouana and C. microphylla . These results indicated that faster seedling growth rate and more efficient water use of C. korshinskii should confer increased drought tolerance and facilitate its establishment in more severe drought regions relative to C. liouana and C. microphylla . Abstract : Increasing drought stress had a significant effect on many aspects of seedling performance in all species, but the physiology and growth varied with species in response to drought. Caragana korshinskii exhibited lower sensitivity of photosynthetic rate and growth, lower specific leaf area, higher biomass allocation to roots, higher levels of water use efficiency to drought compared with the other two species.